PRODUCTIVITY OF MAIZE QPM (QUALITY PROTEIN MAIZE) IN GUNUNGKIDUL - al KS, Prajitno; Sarjiman, Sarjiman; Purwaningsih, Heni; Sudaryanto, B (Agros Journal of Agriculture Science, 2005)
Productive Ability of maize QPM require to be tested in Gunungkidul. Research was conducted at up land in Menggoran 2, Bleberan, Playen, Gunungkidul at rained season. Used Split Plot Design with three replication. The main plot are fertilized include: (A) Urea 300 kg + 200 kg SP36 + KCL 100 kg/ ha, and (B) Urea 50 kg + 100 kg SP36 + KCL 150 kg + organic manure 2 ton / ha, while the Sub plot are maize varieties (1) Srikandi Kuning, (2) Bisma, (3) Srikandi Putih, (4) Sukmaraga and (5) BSKN Genotype. Distance plant the maize 70 x 20 cm, defended one crop of every clump. Wide plot each treatment 4,2 x 5 m. Result of research showed that crop with the fertilization treatment (A) its result is compared treatment (B) is 5.05 and 3.80 ton / ha cob pare the moment harvest. While weight trunk of tree above cob at the harvesting of crop not differ the reality that is 7.86 and 7.25 ton / ha. Contribution Trunk of tree maize above of cob for the feed of computable, if beef cattle weight 500 kg by ration 10% from body weight / day hence the maize trunk of tree can be given as feed beef cattle as much 145 - 157 tail. Among five varieties of examine maize, maize most sensitive to bulai disease, but own the excellence feel its rice is cozier and taken a fancy by the farmer compared the other variety.